Green Chemistry Approaches in Medicinal Chemistry - Basha, S. Farook (AG Volumes, 2025)
One area of study that has gained global interest in analytical chemistry is "green chemistry." Green analytical innovations have been put forward to reduce toxicity without compromising analytical performance. This could be shown at every stage of the analysis by reducing operational risk and contamination of the environment via reduced chemical use and waste production. In this article, review the various researcher’s study on green chemistry approaches in medicinal chemistry. The article concluded that green nanotechnology plays a crucial role in therapeutic advancements, including antidiabetic and anticancer treatments, by facilitating targeted drug delivery with reduced toxicity to healthy tissues. The development of green analytical methodologies, assessed through tools like GAPI and Eco-Scale, further supports sustainable pharmaceutical practices. green chemistry offers a sustainable approach to pharmaceutical R&D, reducing environmental impact while maintaining high efficacy in drug design. With continued innovation and investment, green chemistry is set to transform medicinal chemistry, ensuring safer and more sustainable drug development for the future.